(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
One of the most comprehensive urban transformation programs in the world, India’s Smart City Mission (SCM) began in 2015 with the goal of enhancing citizens’ quality of life via the implementation of technology-driven governance, sustainable infrastructure, and development that is centered on them. Although it is gaining traction on a national level, the results of its implementation range greatly across cities because of variations in administrative capabilities, governance approaches, and institutional structures. The Smart City Mission in Delhi is examined in this paper, which sheds light on its complicated scenario characterized by overlapping authorities, fragmented institutional duties, and operational issues. The study analyzes the effects of Delhi’s multi-layered governance structure on policy implementation, scalability, and public participation using a qualitative research approach that is based on secondary data from government reports, CAG audits, policy papers, and academic literature. The results reveal that although the Integrated Command and Control Centre (ICCC), smart mobility solutions, digital classrooms, and smart surveillance were all part of the high-visibility projects brought about by the Smart City interventions administered by the NDMC, these accomplishments are still limited to the NDMC zone, which covers only 3% of the city. The city-wide implementation was impeded by things like uncertain property ownership, limited public input, persistent administrative fragmentation, and a top-down planning strategy. Policy results are improved by unified governance, consistent community involvement, and clear institutional frameworks, as shown by comparative findings from Bhubaneswar. Delhi shows technical progress in certain areas, but the report says that overall, the city’s model shows how far policy goals are from being achieved in practice. To ensure that smart city development becomes more inclusive, egalitarian, and scalable throughout India’s urban environment, it is vital to strengthen inter-agency coordination, institutional capacity, participatory planning, and outcome-driven monitoring frameworks.